English Education System in International Marketing Based on Digital Marketing - Puspaningtyas, Meinarti; Irawan, Cahya Budi; Castellano, Ana; yanto, Danang dwi gusti fajar (Asia Pacific Journal of Management and Education (APJME), 2022)
Our aim is to investigate the concept in previous research on English Language Education towards digital-based marketing. We use Content Analysis to compile scientific articles from emerald, Science Direct, and Korean science as well as books written by experts in the field of English Education and Marketing. Digitalization is very important for companies and society to adapt. This digitalization is forcing organizations to explore new possibilities while continuing to use existing technologies in established companies. Companies need a marketing system to support the business. The ethical marketing system adopts an attitude that is consistent with the ethical and sustainable marketing concept and demonstrates courteous and ethical behavior to increase sales.